Assessment of dental plaque coverage by Quantitative Light-induced Fluorescence (QLF) in domestic short-haired cats. (April 2017) - Marshall-Jones, Zoe V.; Wallis, Corrin V.; Allsopp, Judi M.; Colyer, Alison; Davis, Ian J.; Holcombe, Lucy J.
Abstract: Dietary means of reducing plaque and calculus deposits are frequently sought for the maintenance of oral health in cats and dogs. In the development of such products sensitive, reliable, reproducible methods of measuring plaque and calculus are key. The aim of this study was to assess Quantitative Light-induced Fluorescence (QLF™) for the detection of dental plaque coverage in cats compared to the modified Logan and Boyce technique. The techniques were utilised in a crossover study, which compared two diets for their effect on plaque deposition in a cohort of 24 adult cats. Analysis of the effect of diet on plaque coverage by both the modified Logan and Boyce technique and QLF showed a significant effect of feeding regime ( p  = 0.024 and p  ≤ 0.0001, respectively) with good agreement between the techniques in the percentage reduction of plaque accumulation. A within study assessment of QLF demonstrated excellent intra-operator repeatability (coefficient of variation 2.2%). Similarly, inter-operator reproducibility was also good (coefficient of variation 2.3%). A retrospective analysis, using the data to estimate the sample size required for at least 90% power to detect a 15% difference between treatments in a two-way crossover study, established that 10 cats would be sufficient for plaque measurement by QLF, while assessment by the modified Logan and Boyce method required over 30 cats. QLF was determined to be a reliable, reproducible method for the assessment of plaque deposition in cats and requires fewer subjects for the detection of differences between treatment effects compared to the modified Logan and Boyce method. Highlights: Quantitative Light-induced Fluorescence (QLF) technology has been developed for the detection of dental plaque coverage in cats Plaque measurement by QLF demonstrated excellent intra-operator repeatability and inter-operator reproducibility QLF has the advantage of requiring fewer cats for the detection of differences between treatment effects compared to the modified Logan and Boyce method of plaque measurement